PENGARUH VITAMIN B2 (Riboflavin) TERHADAP DAYA TAHAN SPERMATOZOA DOMBA PADA SUHU KAMAR - Widjaja, Nilawati (Universitas Djuanda Bogor, 2011)
This study aims to understand the effect of vitamin B2 (Riboflavin) toward mortality and goat spermatozoa percentage of life in room temperature. The study method using experiment method with Rancangan Acak Kelompok (Group Random Program) in time series with 5 Riboflavin additional treatments and 6 ejaculates as a group. The treatment is concentration of vitamin B2 (PO = control) PO = 0 Î¼g/ml, P1 = 1 Î¼g/ml, P2 = 4 Î¼g/ml, P3 = 7 Î¼g/ml, and P4 = 10 Î¼g/ml. The variable that observed is motility and viability. The observation is conducted after dilution WO = 0 hour, W1 = 2 hours, W2 = 4 hours, W3 = 6 hours, and W4 = 8 hours. The study result shows that treatment adding vitamin B2 (Riboflavin) in Tris dilution under room temperature has no significant differences (P>0,05) toward motility and life percentage. Time period of treatment has significant impact (P<0,01) toward motility and viability. There is no interaction between treatment and observation time period (P>0,05).